AirMeasurer: open‐source software to quantify static and dynamic traits derived from multiseason aerial phenotyping to empower genetic mapping studies in rice. Issue 4 (28th July 2022) - Sun, Gang; Lu, Hengyun; Zhao, Yan; Zhou, Jie; Jackson, Robert; Wang, Yongchun; Xu, Ling‐xiang; Wang, Ahong; Colmer, Joshua; Ober, Eric; Zhao, Qiang; Han, Bin; et al.
Summary: Low‐altitude aerial imaging, an approach that can collect large‐scale plant imagery, has grown in popularity recently. Amongst many phenotyping approaches, unmanned aerial vehicles (UAVs) possess unique advantages as a consequence of their mobility, flexibility and affordability. Nevertheless, how to extract biologically relevant information effectively has remained challenging. Here, we present Air Measurer, an open‐source and expandable platform that combines automated image analysis, machine learning and original algorithms to perform trait analysis using 2D/3D aerial imagery acquired by low‐cost UAVs in rice ( Oryza sativa ) trials. We applied the platform to study hundreds of rice landraces and recombinant inbred lines at two sites, from 2019 to 2021. A range of static and dynamic traits were quantified, including crop height, canopy coverage, vegetative indices and their growth rates. After verifying the reliability of AirMeasurer‐derived traits, we identified genetic variants associated with selected growth‐related traits using genome‐wide association study and quantitative trait loci mapping. We found that the Air Measurer ‐derived traits had led to reliable loci, some matched with published work, and others helped us to explore new candidate genes. Hence, we believe that our work demonstrates valuable advances in aerial phenotyping and automated 2D/3D trait analysis, providing high‐quality phenotypic information to empower genetic mapping for crop improvement. Abstract : See also the Commentary on this article by Yang & Zhai, 236 : 1229–1231 .